Pengenalan Literasi Keuangan dan Aplikasi Keuangan Digital pada Gen Z di Kecamatan Banjarmasin Utara - Risky Aulia Handayani; Dinda Arum Sekarsari; Della Prastika Ayudha; Mahmudah Mahmudah; Mutiara Azzahra; Sudirwo Sudirwo; Anna Nur Faidah (Pelayanan Unggulan : Jurnal Pengabdian Masyarakat Terapan, 2025)
This community service program aims to strengthen financial literacy and digital finance competencies among Generation Z in the North Banjarmasin District. The program involved 15 participants aged 18–25 years and was implemented through a combination of lectures on fundamental financial literacy, practical workshops using a digital budgeting application, and structured pre-test and post-test assessments. Findings from the evaluation indicate a substantial improvement in participants’ financial management practices, particularly in financial recording habits, which increased from 46.7% to 93.3% after the intervention. Additionally, participants reported high perceived ease of use (80%) and strong satisfaction with the budgeting application (mean score = 4.33). They also expressed a high intention to continue utilizing digital financial tools in their daily financial activities. These outcomes reinforce the relevance of the Unified Theory of Acceptance and Use of Technology (UTAUT) and the Theory of Planned Behavior (TPB), which highlight the influence of perceived usefulness, perceived ease of use, attitudes, and behavioral control in technology adoption. Overall, the program proved effective in enhancing knowledge, practical skills, and responsible financial behavior among Generation Z, equipping them to navigate digital financial management more confidently and independently.